The Application of Drinking Boiled Turmeric Water to Relieve Pain in Gastritis Patients - Susi Nopita Mayang Sari; Turochman, Hidayat (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Gastritis is a health disorder related to the digestive process, especially the stomach. Contractions in the stomach can cause continuous damage throughout a person's life. If the stomach is frequently empty, it can also lead to damage because the stomach will keep contracting, causing the stomach lining to become scratched and wounded, and these wounds will undergo an inflammatory process. Gastritis is inflammation of the stomach mucosa that often occurs due to irregular eating habits. One of the causes of gastritis is the behavior of sufferers who do not pay attention to their health, especially the food they consume daily. Purpose of writing: The author is able to gain real experience in caring for and administering turmeric decoction. Research method: Descriptive method and literature study. The descriptive method is a case study approach by looking at a single family case and applying the intervention of giving turmeric decoction as well as providing nursing care. The descriptive method is a case study approach by taking one family case and applying the intervention of giving boiled turmeric water as well as providing nursing care. Research results: After administering boiled turmeric water for 3 days, 3 times a day after meals, the family of Mrs. S, particularly Mrs. S with Gastritis, experienced a decrease in pain, initially 4-5, which dropped to 0-1. Conclusion: The administration of boiled turmeric water in a family with Gastritis was carried out smoothly, namely the family's knowledge about Gastritis increased, there was a decrease in pain scale from 4-5 to 0-1, and the family was able to care for members suffering from Gastritis.